Children sustain high levels of skin DNA photodamage, with a modest increase of serum 25‐hydroxyvitamin D3, after a summer holiday in Northern Europe. (1st October 2018) - Narbutt, J.; Philipsen, P.A.; Lesiak, A.; Sandberg Liljendahl, T.; Segerbäck, D.; Heydenreich, J.; Chlebna‐Sokol, D.; Olsen, P.; Harrison, G.I.; Pearson, A.; Baczynska, K.; Rogowski‐Tylman, M.; et al.
Summary: Background: Childhood solar ultraviolet radiation (UVR) exposure increases the risk of skin cancer in adulthood, which is associated with mutations caused by UVR‐induced cyclobutane pyrimidine dimers (CPD). Solar UVR is also the main source of vitamin D, essential for healthy bone development in children. Objectives: To assess the impact of a 12‐day Baltic Sea (54° N) beach holiday on serum 25‐hydroxyvitamin D3 [25(OH)D3 ] and CPD in 32 healthy Polish children (skin types I–IV). Methods: Blood and urine were collected before and after the holiday and assessed for 25(OH)D3 and excreted CPD, respectively, and personal UVR exposure was measured. Diaries were used to record sunbathing, sunburn and sunscreen use. Before‐ and after‐holiday skin redness and pigmentation were measured by reflectance spectroscopy. Results: The average ± SD daily exposure UVR dose was 2·4 ± 1·5 standard erythema doses (SEDs), which is borderline erythemal. The mean concentration of 25(OH)D3 increased (× 1·24 ± 0·19) from 64·7 ± 13·3 to 79·3 ± 18·7 nmol L −1 ( P < 0·001). Mean CPD increased 12·6 ± 10·0‐fold from 26·9 ± 17·9 to 248·9 ± 113·4 fmol μmol −1 creatinine ( P < 0·001). Increased 25(OH)D3 was accompanied by a very much greater increase in DNA damage associated with carcinogenic potential. Overall, skin type had no significant effects on behavioural, clinical or analytical outcomes, but skin types I/II had more CPD (unadjusted P = 0·0496) than skin types III/IV at the end of the holiday. Conclusions: Careful consideration must be given to the health outcomes of childhood solar exposure, and a much better understanding of the risk–benefit relationships of such exposure is required. Rigorous photoprotection is necessary for children, even in Northern Europe.